using algebraic identities
in Algebra 2 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

Given (a-b)^2 = 2(a^2+b^2)

We know that, (a-b)^2 = a^2 + b^2 - 2ab

So given equation can be written like this

a^2 + b^2 - 2ab = 2(a^2 + b^2)

a^2 + b^2 - 2ab = 2a^2 + 2b^2

-2ab = a^2 + b^2

a^2 + b^2 + 2ab = 0

(a+b)^2 = 0 (  (a+b)^2 = a^2 + b^2 + 2ab)

a + b = 0

a = -b

Hence its proved

Do you find hard to solve these kind of problems? Algebra solver gives you a simple ways and step by step explanation, it will really help you in your homework and upcoming exams.

by Level 8 User (30.1k points)

Related questions

1 answer
asked Sep 14, 2013 in Algebra 1 Answers by anonymous | 600 views
1 answer
1 answer
1 answer
1 answer
asked Jun 23, 2013 in Algebra 1 Answers by automit Level 1 User (140 points) | 1.1k views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
87,548 questions
99,681 answers
2,417 comments
465,902 users